2018
DOI: 10.1111/pan.13360
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound reclassification of chest X‐ray data after pediatric cardiac surgery

Abstract: Lung ultrasound is feasible and accurate for the diagnosis of common pulmonary conditions after pediatric cardiac surgery, allowing reclassification of chest X-ray findings in a significant number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…(Ann Thorac Surg 2020;109:178-84) Ó 2020 by The Society of Thoracic Surgeons L ung ultrasound (LUS) is a noninvasive, easy, and fast technique for the evaluation of pulmonary disease in children, especially in the acute setting. [1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Ann Thorac Surg 2020;109:178-84) Ó 2020 by The Society of Thoracic Surgeons L ung ultrasound (LUS) is a noninvasive, easy, and fast technique for the evaluation of pulmonary disease in children, especially in the acute setting. [1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery. [4][5][6][7] These studies have shown diagnostic accuracy of LUS for pulmonary complications after surgery including pleural effusion, atelectasis, pneumothorax, and pneumonia.…”
mentioning
confidence: 99%
“…LUS has been used to diagnose a variety of lung diseases such as pneumonia, pleural effusion, and consolidation, with high accuracy. 17,18,23 Our study showed the sensitivity and accuracy of LUS However, LUS has the advantage of being more sensitive than CXR in pleural effusion, pneumothorax, and consolidation in previous study. 17 Furthermore, one study showed that CHD newborns with suspected PO had a significant increase of B lines in LUS, before PO was detected by CXR, by echocardiography or by clinical examination.…”
Section: Discussionmentioning
confidence: 52%
“…LUS has been used to diagnose a variety of lung diseases such as pneumonia, pleural effusion, and consolidation, with high accuracy . Our study showed the sensitivity and accuracy of LUS were 94% and 95%, respectively, while CXR had only 74% sensitivity and 63% accuracy, for the diagnosis of PO.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation